Prevalence and anatomical significance of the persistent median artery: A cadaveric study - Connor Ellis; Drew Thibault; Josh Lencke; Laurieanne D. Hemric (PLoS ONE, 2025)
Purpose The median artery is the initial, yet transient, vascular supply to the palm originating from the brachial artery during development. This artery generally regresses as radial and ulnar arterial supply become prominent; however, this regression does not always occur. This study seeks to illuminate the prevalence of the persistent median artery in the adult population, as well as describe the vascular consequences secondary to the presence of this artery. Methods Antebrachial and palmar dissections were performed on 56 adult cadavers (112 upper extremities). Prevalence of palmar and antebrachial-type persistent median artery were recorded separately. Arterial diameters of radial and ulnar arteries were measured and statistically examined with and without the co-presence of a persistent median artery. Results A persistent median artery was present in 43% of the upper limbs included in this study. 28% of the population were of the antebrachial-type, while 15% were of the palmar-type. The overall mean arterial diameters of the radial artery were 3.13 mm ( ± 0.57 mm; n =  52) without any persistent median artery present, compared to 3.09 mm ( ± 0.56 mm; n =  34) with persistent median artery co-presence. The mean diameters for the ulnar artery were 2.75 mm ( ± 0.53 mm; n =  53) without co-presence of persistent median artery and 2.86 mm ( ± 0.65 mm; n =  36) with co-presence. Conclusion This and other studies have demonstrated the prevalence of this persisting embryologic artery to be quite high. An understanding of the characteristics and significance of this artery in the adult population is necessary to surgeons operating on the carpal tunnel or distal antebrachium.